A will in search of a way: philanthropy in education in Perú (2019)
The ingredients for strong and strategic institutionalised philanthropy exist in Latin America: charitable traditions, rapid wealth creation from the global commodity boom and weaker than expected state social services (Hauser Center, 2016; Johnson, 2018; Sanborn & Portocarrero, 2005). Peru is an exemplary regional case (León & Bird, 2018; Portocarrero, Sanborn, Cueva & Millán, 2002). Due mostly to increased mining exports in the early 2000s, the World Bank reclassified Peru as an upper middleincome country, which prompted overseas development assistance (ODA) organisations, comprised of multilateral and private institutions, to shift resources outside the country and call on local entities to better channel wealth to address social issues. Local philanthropists sought to meet the challenge, with over half of the country’s philanthropic organisations founded after 2000.